PELATIHAN PEMBUATAN SHIBORI BUSANA OUTER SCARF PADA REMAJA PUTRI DI DESA PULUNGAN - Ria Andriani Mukti; Dita Ayu Agatha; Desi Ayu Novitasari; Annisa Dwi Yanti; Mulia Dwi Rizky; Mirna Frisca Yulianingtyas (Jurnal Penamas Adi Buana, 2023)
Shibori batik is one of the batiks whose manufacturing process is carried out using the jumputan technique which produces various colors and motifs. The Real Work Lecture Team (KKN) at PGRI Adi Buana University Surabaya in Pulungan Village, held shibori-making training which was attended by Young Women from Pulungan Village with the aim of empowering creative economic potential. The event was aimed at representatives of young women from Pulungan Village. The purpose of this training is to provide skills for entrepreneurs in the form of product creation to sales. The method used is a demonstration method which provides 5 stages, namely direction, guidance and teaching regarding manufacturing practices. The implementation mechanism is divided into 5 stages, namely: planning, directing, guidance, practical teaching and monitoring and evaluation. This training was held in early January 2023. The Young Women of Pulungan Village were very enthusiastic about the training on making shibori so it ran smoothly and got a good response. The result of this training is an outer scarf product with a shibori motif that is ready to be marketed